2020
DOI: 10.22373/ej.v7i2.6472
|View full text |Cite
|
Sign up to set email alerts
|

Efl Learners' Difficulties in the Structure and Written Expression Section of Toefl Test in an Indonesian University

Abstract: This study examined the English for Foreign Language (EFL) learners' difficult topics in the structure and written expression section of the TOEFL Prediction Test, and reasons why they consider that these topics were difficult. The mixed-method research design was used in this study. Fifteen participants were selected through purposive sampling mechanism from the seventh-semester students of Department of English Language Education, Universitas Islam Negeri Ar-Raniry who have participated in the TOEFL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…There are a variety of issues and reasons that contribute to kids' difficulty with language, including the following: Understanding tough-level language is becoming difficult. The birth of a feeling of maleness in one's own self, as well as the ability to remember and comprehend terminology In ordinary life, vocabulary (while speaking in English) is seldom used (Akmal et al, 2020). Based on some of the problem ideas and factors mentioned above, it can be explained that there are four ways to understand vocabulary: (1) Form is studying, listening and repeating, listening for specific phonological information (consonants, vowel sounds, syllable sources, Copyright © 2021, Journal of Asian Multicultural Research for Educational Study, Under the license CC BY-SA 4.0 stress patterns), looking at or observing the written for shape, first and last letters, letters clusters, spelling, noticing grammatical information, and copying and organizing; (2) Content is studying, listening and repeating, listening for specific phonological (2) Pronunciation is also known as pronunciation in English or pronunciation in the English language.…”
Section: Vocabularymentioning
confidence: 99%
“…There are a variety of issues and reasons that contribute to kids' difficulty with language, including the following: Understanding tough-level language is becoming difficult. The birth of a feeling of maleness in one's own self, as well as the ability to remember and comprehend terminology In ordinary life, vocabulary (while speaking in English) is seldom used (Akmal et al, 2020). Based on some of the problem ideas and factors mentioned above, it can be explained that there are four ways to understand vocabulary: (1) Form is studying, listening and repeating, listening for specific phonological information (consonants, vowel sounds, syllable sources, Copyright © 2021, Journal of Asian Multicultural Research for Educational Study, Under the license CC BY-SA 4.0 stress patterns), looking at or observing the written for shape, first and last letters, letters clusters, spelling, noticing grammatical information, and copying and organizing; (2) Content is studying, listening and repeating, listening for specific phonological (2) Pronunciation is also known as pronunciation in English or pronunciation in the English language.…”
Section: Vocabularymentioning
confidence: 99%
“…Handayani (2019) also carried out similar research to firstgrade nursing students and found 8 lexicogrammatical topics (word order, parallel structure, singular and plural nouns, missing and extra words, articles, comparative and superlative, word choice, and word form) that were considered the most difficult based on students' test performance according to the students. Akmal et. al.…”
Section: Figure 1:the Lexicogrammar Clinementioning
confidence: 99%
“…If there are any studies carried out focusing on the Structure and Written Expressions section, they were limited to investigating the problems that the students faced in terms of linguistic factors (Akmal et al, 2020;Nasution, 2019;Putra, 2020;Syahrin, 2020;Tangkelangi, 2020). These previous studies tried to identify the grammatical items that posed the most challenging problems for the participants.…”
Section: Introductionmentioning
confidence: 99%